Measuring government performance in public opinion surveys in Africa: Towards experiments? - Michael Bratton (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
In examining the study of government performance, this paper asks whether field experiments can improve the explanatory precision of results generated by public opinion surveys. Survey research on basic health and education services sub-Saharan Africa shows that the perceived 'user friendliness' (or ease of use) of services drives popular evaluations of government performance. For the reliable attribution of causality, however, surveys and field experiments, combined in a variety of mixed research designs, are more rigorous and reliable than either method alone. The paper proposes a menu of such designs.
Keywords: H4; I00; I18; I25; 330; government performance; surveys; experiments; health; education; Africa